DESIGNING ENTION APPLICATION BASED ON ANDROID IN PRONUNCIATION LEARNING - Bahtiar, Yuyun; Rabani, Ahmad (Research on English Language Education, 2023)
In the world of technology, education is very important in English learning media. In this case, many students have difficulty understanding English learning, especially in pronunciation. Therefore, the author makes an English learning application media to help students pronounce English properly and correctly. At this stage, the author uses the R&D (research and development) method by adapting ADDIE (analyze, design, develop, implement, evaluate) in this development the authors get 91,6% data results in media validation which can be characterized as very good. In the results of the validation of the material, the author gets 75% data results which are categorized as good. In addition, at the implementation stage, the responses from students received 78,1% of data which can be characterized as good. From the whole data, it can be said that this ENTION (English in Action Application) is possible to use as a learning media at Islamic Senior High School At-Taufiq Bogem, Diwek.